(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The density and distribution of immature and adult Scaphoideus titanus Bali on yellow sticky traps was studied in the two vineyards of Castelrotto (Canton of Ticino, Switzerland) and Ghemme (near the town of Novara, Italy). The Aéroxon traps placed horizontally within the plant canopy is most efficient to catch S. titanus adults since they are more mobile then the immature forms. The smallest number of traps assuring a desired reliability of the estimate is calculated on the basis of formai probabilistic statements: half of the lenght of the confidence interval is equal to a proportion D of the standard error of the mean, and the confidence interval should include the true mean with a probability P. Thereby, the variance is expressed as a function of the mean according to Taylor’s power law, and the distribution of both the adults and the immature individuals was aggregated. For the purpose of this study, D=0.3 and P=0.9 were assumed to produce reliable estimates. Accordingly, 9 traps are sufficient if the density is 10 specimens per trap, but 41 traps are required fora density of 1 individuals per trap. The two vineyards under study were divided into 6 blocks. Since there were generally no significant differences (P < =O. 05) between these blocks a simple random placement of traps can be envisaged. The method is useful for monitoring S. titanus populations. It permits for example a better estimate of the trials of pesticide applications.